Pengaruh Organizational Citizenship Behavior (OCB) dan Motivasi Kerja terhadap Kinerja Karyawan pada Kantor Komite Olahraga Nasional Indonesia (KONI) Jawa Barat - Gultom, Sun Tesalonika; Dian Lestari (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of Organizational Citizenship Behavior (OCB) and work motivation on employee performance at the Indonesian National Sports Committee (KONI) West Java Office. The research method used was a quantitative approach with descriptive verification. The population in this study consisted of 45 employees, who were also sampled using saturation sampling. Data collection was conducted using a questionnaire that was tested for validity and reliability, while data analysis used multiple linear regression with the help of SPSS version 26. The results showed that OCB and work motivation have a positive and significant effect on employee performance, both partially and simultaneously, with a coefficient of determination of 42.2%. The conclusion of this study is that increasing OCB and work motivation can simultaneously improve employee performance at the KONI West Java Office.   Keywords: OCB, Work Motivation, Employee Performance, Organizational Behavior